Immunological Effects of Oncolytic Coxsackievirus A21 on the Mouse Model of Colorectal Cancer - Reza Karbalaee; Morteza Izadi; Bahman Jalali Kondori; Ruhollah Dorostkar; Seyed Morteza Hosseini; Hadi Esmaeili Gouvarchin Ghaleh (Negah Institute for Scientific Communication, 2022)
Introduction: Cancer is one of the most prevalent causes of death worldwide. In terms of global mortality, colorectal cancer (CRC) is the second most prevalent cancer form. Typically, the initial step in treating colon cancer is surgery to remove tumors. A referral for further treatments like chemotherapy and radiation therapy could also be made. However, because of medication resistance and a lack of focused treatments, it is constantly necessary to create new cancer therapy methods. This investigation examined the impact of the oncolytic coxsackievirus A21 (CVA21) on a mouse model of colorectal cancer. Methods: Thirty BALB/c mice were divided into three equal groups randomly. 5×106 CT-26 cells, a colonic carcinoma cell line, were injected into the left flank of each animal to simulate colorectal cancer. Group A was treated with PBS once the palpable tumor was discovered (18 days later), group B was treated with the oncolytic CVA21 (106 TCID50/mL, twice at one-week intervals), and group C was treated with 5-fluorouracil (5-FU), 50 mg/kg, twice at one-week interval. The mice were euthanized ten days after the final injection, and the spleens were removed and examined under sterile circumstances to determine the lymphocyte proliferation index, LDH, NO, IL-4, IL-10, IFN-γ, and TGFβ production levels. A significant P˂0.05 level was considered in all evaluations. Results: The current study's findings showed that when compared to the control group, treatment with CVA21 increased NO (30.5±4.10 µM), LDH (58.18±4.61 %), and IFN-γ (44.82±3.72 pg/mL) levels and significantly decreased the secretion of IL-4 (30.07±3.34 pg/mL), IL-10 (62.11±5.69 pg/mL), and TGF-β (56.66±6.88 pg/mL). Conclusion: The CVA21 treatment for colorectal cancer appears to have some potential benefits. In other words, the study's findings demonstrated that using oncolytic viruses also activates the innate immune system by raising levels of nitric oxide and the acquired immune system. The favorable benefits of the combination may also be attributable to immunological divergence in the current study from anti-inflammatory cytokines (such as IL-4, IL-10, and TGF-β) to pro-inflammatory cytokines, such as IFN-γ.